SYSTEMATIC ANALYSIS OF PERSPECTIVE TRENDS IN ECOLOGICAL AND BIOLOGICAL STUDIES OF THE CASPIAN SEA - G. M. Abdurakhmanov; A. F. Sokolsky; G. A. Kuanysheva; E. A. Sokolskaya; Yu. M. Brumshteyn (Юг России: экология, развитие)
RETRACTED ARTICLEAim. The main purpose of the ecological and biological research (EBR) of the Caspian Sea is the information and technical support of decision-making to ensure the environmental management in the region taking into account the increase of anthropogenic impact and change in climatic conditions.Methods. As a basis, we have adopted the method of theoretical and mathematical generalization of a number of scientific papers and systematic analysis of the proposed solutions.Results. Analysis and mathematical processing of published literature sources has convincingly demonstrated the need for international cooperation to optimize the ecological and biological research. It has also confirmed the usefulness of the ecological and biological studies of the Caspian Sea in different directions, and the distribution of effort (cost) between them requires coordinated management.Conclusion. It is shown that the data obtained by EBI have both rapid and long-term value. In the future, it is rational to develop suitable approaches to unified structuring of the EBR data, including their spatial and timing. An important task is to create a single interstate information space on the results of EBR using information and communication technologies.